PENEMUAN HUKUM OLEH HAKIM DALAM PERKARA PIDANA BERDASARKAN UNDANG-UNDANG NOMOR 48 TAHUN 2009 TENTANG KEKUASAAN KEHAKIMAN - Rian Kurniawan; Erdianto Effendi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The discovery of the law is according Sudikno Mertokusumo , typically defined as the process of law-making by a judge or other officer law officer who was given the task of implementing the law or apply the common law rule against concrete legal events . But especially those in the criminal case judges in Indonesia are faced with a dilemma where on the one hand he had to perform legal discovery , but on the other hand he was blasted by a tight principle of legality that does not allow any punishment unless there is a law that regulates the actions that can be convicted . The purpose of this study , to determine the legal discovery in criminal cases based on Law No. 48 Year 2009 on Judicial Power , and to determine the barriers to discovery of the law by a judge in a criminal case based on Law No. 48 Year 2009 concerning Judicial Authority .This type of research is a normative legal research or can be referred to as the doctrinal legal research . The discovery of the law in criminal cases based on Law No. 48 Year 2009 concerning Judicial Authority , still has some issues ,one of which is the discovery of this law does not have a standard or special rules , such as law , legal discovery despite having some of the methods proposed by the legal experts , and the judges , but for its use is left entirely to the judge overseeing the case , the lack of legal discovery in criminal cases is still espoused understand the principle of legality set forth in Article 1 paragraph (1) Indonesian Criminal Code Plus after the Constitutional Court ruled in its decision No. 003 / PUU - IV / 2006 on July 25, 2006 which has been decided to remove the use tort understand the material in a positive sense . Efforts to overcome the weaknesses or shortcomings of this is to make a clear and unequivocal rule of the ability of judges to perform legal discovery , especially in criminal cases in Indonesia , and there are clear rules regarding the methods of the invention legitimate law and recognized by the laws of Indonesia . Soon the passing of the Bill Indonesian Criminal Code , to make it clear that in addition to the written law / legislation , there is also customary law recognized certain in the Draft Bill and the judges do not hesitate to dig , and find a sense of justice that live in society .Keywords : The Discovery of Law - Judge – Phedofilia- Criminal Case